Interrupt or reinforce? The impact of timeout on momentum in basketball game - Qiu, Mingjia; Zhang, Kaimin; Chao, Yafei; Zhang, Mingxin (Frontiers in Psychology, 2025)
IntroductionTimeouts are often viewed by coaches as an important means of intervening in a game, but their impact on the game’s momentum still lacks empirical research. This study aims to evaluate the impact of timeouts on momentum, defined as excellent offensive and defensive performance over a short period in basketball games, and to analyze the moderating role of contextual factors.MethodsA total of 4,051 timeouts from 1,235 elite professional basketball games were analyzed. Momentum was measured at short (48 s), medium (96 s), and long (144 s) intervals before and after each timeout. T-test (or Wilcoxon signed-rank test) were used to examine the difference in momentum before and after timeouts, and linear mixed models were employed to assess the impact of contextual factors.ResultsTimeouts significantly increased team momentum, particularly when the team was in a disadvantaged status. Conversely, when the team was in an advantageous status, timeouts tended to reduce momentum. Contextual factors significantly moderated the effects of timeouts: better effects were observed during regular game periods, whereas timeouts were less effective in the last 5 min or against high-level opponents. Moreover, the medium- and long-term effects of timeout are more susceptible to contextual modulation, whereas short-term effects remained relatively stable.DiscussionTimeouts are an important intervention to influence momentum in basketball, and their effectiveness depends on game context and team status. These findings provide practical insights for coaches, suggesting that timeout strategies should be tailored to game conditions and situational dynamics to enhance their effectiveness.